2013
DOI: 10.1186/1471-2172-14-s1-s13
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the humoral immune response and cross reactivity against Mycobacterium tuberculosis of mice immunized with liposomes containing glycolipids of Mycobacterium smegmatis

Abstract: Mycobacterium smegmatis (Ms) is a nonpathogenic mycobacteria of rapid growth, which shares many characteristics with Mycobacterium tuberculosis (MTB), the major causative agent of tuberculosis. MTB has several cell wall glycolipids in common with Ms, which play an important role in the pathogenesis of tuberculosis and the induction of a protective immune response against MTB infection in some animal models. In this study, the humoral immune response and cross reactivity against MTB, of liposomes containing a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…A higher reactivity of IgG antibodies against this formulation was detected in patients with pulmonary TB, compared with healthy individuals, which suggests the expression of similar or cross-reactive epitopes during the active infection with Mtb in humans [ 10 ]. When the total lipid extract of Ms was formulated in liposomes containing commercial lipids without adjuvants, a similar induction of specific and cross-reactive IgG response against Mtb was obtained [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A higher reactivity of IgG antibodies against this formulation was detected in patients with pulmonary TB, compared with healthy individuals, which suggests the expression of similar or cross-reactive epitopes during the active infection with Mtb in humans [ 10 ]. When the total lipid extract of Ms was formulated in liposomes containing commercial lipids without adjuvants, a similar induction of specific and cross-reactive IgG response against Mtb was obtained [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…Taking into consideration the induction of specific IgG antibodies and the elicitation of cross-reactive immune responses against Mtb after immunization with formulations containing lipids of Ms in mice [ 10 , 11 ], the role of specific antibodies in the protection induced by these formulations cannot be ruled out. The contribution of specific antibodies in protection against TB is a subject of debate, but a growing body of evidence supports the potential role of antibodies in the protection against TB [ 27 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that serum antibodies may have protective effect in animal models of tuberculosis (39,53). In addition, analysis of the isotypic distribution of immunoglobulin may offer an insight into the possible immunological mechanisms involved in cellular immunity (54).…”
Section: Discussionmentioning
confidence: 99%
“…Humoral immunity has also been demonstrated to have a protective role in mycobacterial infections (39). In order to evaluate the IgG antibody response in immunized mice in the BCG or BCG prime Ad5-CEAB-boosted groups, the titers of IgG in mice were examined at 2 weeks following the final immunization.…”
Section: Antigen-specific T Cell Responsesmentioning
confidence: 99%